2018
DOI: 10.37358/rc.18.11.6674
|View full text |Cite
|
Sign up to set email alerts
|

Study Regarding the Serum Level of Uric Acid and the Metabolic Syndrome

Abstract: The goal of this study is to investigate the relationship between the serum level of uric acid (UA) and metabolic syndrome (MetS) according to age and gender. The study included 395 patients (200 women and 195 men), with a mean age of 53.6�18 years. Hyperucemia (HU) was defined by a serum level UA �7mg/dL in men and � 6mg/dL in women (according to the EULAR guide), and MetS was defined according to the criteria of the International Diabetes Federation (IDF). The prevalence of hyperuricemia in the study lot w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Patients with cardiovascular disease generally present a cumulative of both unmodifiable and modifiable cardiovascular risk factors, and currently the metabolic syndrome is frequently associated with hyperuricemia. In the treatment of hyperuricemia, a diet rich in vegetables and fresh fruits is recommended [48,49]. There is convincing evidence that a cardio-protective diet that includes nuts is an important lifestyle practice for managing the risk of cardiovascular disease [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with cardiovascular disease generally present a cumulative of both unmodifiable and modifiable cardiovascular risk factors, and currently the metabolic syndrome is frequently associated with hyperuricemia. In the treatment of hyperuricemia, a diet rich in vegetables and fresh fruits is recommended [48,49]. There is convincing evidence that a cardio-protective diet that includes nuts is an important lifestyle practice for managing the risk of cardiovascular disease [50].…”
Section: Resultsmentioning
confidence: 99%
“…Data from the literature have shown that frequent walnut consumption is associated with improved risk factors for cardiovascular disease [54,55] and with a lower risk of developing cardiovascular disease [56,57]. Clinical studies have reported beneficial effects of walnut consumption on blood lipids [48], inflammatory parameters, insulin resistance [57,58] and blood pressure [59]. Walnuts are a good source of unsaturated fatty acids and are rich in fiber, minerals (potassium, calcium and magnesium), vitamins (folate and E), phytosterols and polyphenols [58].…”
Section: Resultsmentioning
confidence: 99%
“…Clinical characteristics, the main indications for aortic reconstruction and the time since surgery, associated diseases and risk factors, are illustrated in table 1. In addition to major cardiovascular risk factors (high blood pressure, dyslipidemia, diabetes, smoking), hyperuricemia is currently considered a cardiovascular risk factor, frequently associated with metabolic syndrome [15][16][17].…”
Section: Resultsmentioning
confidence: 99%